Jurisdiction on 'Islamic banking business' in Malaysia: Qua vadis syariah court? - Md Dahlan, Nuarrual Hilal (Institut Kefahaman Islam Malaysia, 2004)
Islamic banking has aroused quite an interest in 1960s and 1970s following the resurgence of Islam in the early twentieth century, and the momentum was spearheaded particularly by the Egyptian Muslim scholars and thinkers such as Muhammad Abduh, Rashid Rida, Hassan Al-Banna and Jamaluddin Al-Afghani Islamic banking eventually got its foothold in Malaysia with the establishment of Bank Islam Malaysia Berhad in 1983. The Islamic banking facilities inevitably expanded to meet and serve the customers' insatiable demand for user-friendly banking facilities and products. These Islamic banking products are Mudharabah which is a general and special investment deposits in the nature of profit sharing between the depositors/customers and the bank acts as the entrepreneur; Wadiah is where the bank simply acts as the safe-keeper of the deposits of the depositors/customers but it may provide returns to the depositors as a gift ('al-Hibah'); Murabahah (partnership and equity financing); ljarah (leasing); Musyarakah (partnership), and Bai' Bithaman Ajil (sale by deferred payment). Due to the increasing demands for these Islamic banking products, Islamic windows (Islamic banking products) were likewise introduced by the conventional banks.